FAKTORâFAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013â2015 - Noor Cholifah, 14.05.62.0023; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
This study examines and analyzes the effects of institutional ownership, asset structure, profitability, and firm size on debt policy at the firm. The population of this research is all manufacturing companies listed on Indonesia Stock Exchange for year of 2013 to 2015. The study employs purposive sampling for data collection.data collected from 2013 to 2015 resulted 238 sample. Method of data analysis of the study is multiple regression analysis. The study found effectinstitusional ownership have a positive effect not significantstruktur asset affect positif the debt policy. Moreover, profitability, companyâs size have a negative effect the debt policy.Keywords: Institusional Ownership, Asset Structure, Profitability, Companyâs Size